Cosmological moduli and non-perturbative production of axions - Robert Wiley Deal; Leia Barrowes; John T. Giblin; Kuver Sinha; Scott Watson; Fred C. Adams (Journal of High Energy Physics)
Abstract Cosmological moduli generically come to dominate the energy density of the early universe, and thereby trigger an early matter dominated era. Such non-standard cosmological histories are expected to have profound effects on the evolution and production of axion cold dark matter and dark radiation, as well as their prospects for detection. We consider moduli-axion couplings and investigate the early history of the coupled system, considering closely the evolution of the homogeneous modulus field, the back-reaction from the axion, and the energy densities of the two fields. A particular point of interest is the enhancement of axion production from modulus decay, due to tachyonic and parametric resonant instabilities, and the implications of such production on the cosmological moduli problem, axion dark radiation, and the available parameter space for axion dark matter. Using an effective field theory approach, WKB-based semi-analytical analysis, and detailed numerical estimates of the co-evolution of the system, we evaluate the expected decay efficiency of the modulus to axions. The effects of higher-order operators are studied and implications for UV-complete frameworks such as the Large Volume Scenarios in Type IIB string theory are considered in detail.